Anglo-American legal ideas in the formation of South American private law: 1820-1870 - Caffera, G (2017)
It is traditionally understood that, following the emancipation of South America from Spain and Portugal, the national private law usually encompassed by the Civil Codes of the newly independent countries was inspired by the French Civil Code, and other civil law models. The aim of this thesis is to explore whether this understanding should be revised in order to account for the influence of Anglo-American law and legal ideas. The thesis proceeds, first, to provide the context for the research: the channels of communication, the actors involved, and the different types of use of Anglo-American legal ideas during the formative period of South-American private law. Then, the three main areas of legislative use and influence of Anglo-American law and legal ideas detected are explored. First, the reform of intestate succession, which was a case of direct, and overt Anglo-American influence. Second, the use of Bentham‟s ideas in the abolition of usury laws and laesio, which was a case of direct and conscious, but unacknowledged influence. Finally, the indirect influence of Blackstone‟s works on the drafting of the rules of statutory interpretation on some South-American Civil Codes. Four conclusions, which contradict the traditional account, are drawn. First, that in the process of creation of South-American private law, not only civil law sources of inspiration were used, but also Anglo-American ones, to a much lesser extent, but with a relevant impact nevertheless. Second, that while the process of formation of South-American private law has been described as a creative one by many legal historians, the influence of Anglo-American ideas in the development of the identity of South-American private law has been ignored. Third, that Anglo-American influence gave South-American private law its own identity, making it more liberal than French law in the three fields mentioned above. Fourth, that even in the face of evidence, academic adherence to the traditional view has resulted in an extraordinary relegation of the topic of this thesis.